2015
DOI: 10.1111/vde.12283
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus otitis in small animals – a retrospective study of 17 cases

Abstract: Aspergillus otitis is uncommon, typically seen as unilateral otitis externa in cats and larger breed dogs with possible risk factors that include immunosuppression and otic foreign bodies; previous antibiotic usage was common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
(63 reference statements)
0
13
0
3
Order By: Relevance
“…That study also showed increased relative abundance of Basidiomycota in dogs with a history of allergic skin disease and, although active OE was not identified in that study's population, historic OE in dogs with allergic skin disease is likely. Aspergillus has been reported as a cause of OE in dogs . Aspergillus was not identified cytologically, but a few sequences attributed to Aspergillus were present in some dogs within each group.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…That study also showed increased relative abundance of Basidiomycota in dogs with a history of allergic skin disease and, although active OE was not identified in that study's population, historic OE in dogs with allergic skin disease is likely. Aspergillus has been reported as a cause of OE in dogs . Aspergillus was not identified cytologically, but a few sequences attributed to Aspergillus were present in some dogs within each group.…”
Section: Discussionmentioning
confidence: 95%
“…Otitis externa (OE), defined as inflammation of the external ear canal, is a common, and often protracted or recurrent, clinical condition in dogs. Dogs may be genetically or anatomically predisposed to this condition or have a primary underlying cause; OE often is perpetuated by micro‐organisms or antimicrobial treatment . Cytological evaluation of the ear canal is an informative and cost‐effective guide for veterinarians to select pathogen‐directed therapy.…”
Section: Introductionmentioning
confidence: 99%
“…About 27% of cases of otitis externa are reported as being caused by fungi, mainly by Malassezia pachydermatis [ 3 ]. Other fungi more or less frequently involved are Aspergillus niger, Aspergillus fumigatus, Aspergillus terreus [ 4 ], and several yeasts, such as Candida albicans [ 5 , 6 ], Candida parapsilosis, Trichosporon cutaneum , and Cryptococcus laurentii [ 7 ], as well as Candida tropicalis [ 6 , 8 ] and Rhodotorula [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Se sabe que la aspergilosis en animales no es una patología frecuente; sin embargo, puede ocurrir en pacientes sanos bajo situaciones de estrés o en condiciones de inmunosupresión iatrogénica o endógena, produciendo desde infecciones localizadas hasta diseminadas, así como reacciones alérgicas (Coyner, 2010;Goodale et al, 2016;Seyedmousavi, 2019). Los pacientes inmunosuprimidos son más susceptibles a una infección diseminada hacia otros órganos como hígado, corazón, páncreas, pulmones (Sykes, 2014), por lo que es recomendable el tratamiento inmediato con medicación antifúngica vía oral y tópica.…”
Section: Discussionunclassified
“…Otro tipo de bacterias pueden estar presentes de forma normal en el canal auditivo, las cuales pueden volverse patógenas debido a una proliferación excesiva. En comparación a hongos filamentosos, existen pocos reportes de infecciones óticas u otomicosis, por ejemplo, Aspergillus niger y A. flavus (Goodale et al, 2016).…”
Section: Introductionunclassified